The balance of estrogen metabolites in breast cancer and the ways of its correction - L. A. Ashrafyan; N. A. Babaeva; I. B. Antonova; O. A. Ovchinnikova; O. I. Aleshikova; T. A. Motskobili; I. N. Kuznetsov (ABV-press, 2015)
Background. A clear relationship is now found between the activity of estrogen metabolites and the development of tumors in estrogen-dependent tissues. Many international and Russian studies could identify a number of compounds involved in the regulation of estrogen metabolites. Indole-3-carbinol is one of these compounds that correct a ratio of 2-hydroxyestrone (2-OHE1) to 16-OHE1. It is a phytonutrient that is contained in Cruciferous vegetables and has antitumor activity. Our investigations used highly purified indole-3-carbinol (Indinol). The ability to identify the role of metabolic syndrome, by applying the current methodological approaches, allowed us to study the effect of highly purified indole-3-carbinol on the level of expression of estrogen metabolites and to attempt to expand views on procedures to prevent and treat breast tumors. Materials and methods. A total of 136 women were comprehensively examined; of them 44 patients formed a group of those with morphologically verified hormone-independent breast cancer (BC) and 42 patients were a group of those with hormone-dependent BC. A control group included 50 women without signs of breast disease. In all the patients, body mass index was calculated; the ratio of urinary estrogen metabolites (2-ОНЕ1/16α-ОНЕ1) was quantified; and biopsy specimens and operative material were histologically and immunohistologically studied. Results. The BC patients were noted to have the high expression of 16α-OHE1 and the low values of 2-OHE1 (ratio, 0.42) as compared to the control group (2.09), which was an important component of metabolic syndrome. The BC patients had the high level of concomitant endocrine metabolic disturbances with the high body mass index, which reflected the clinical manifestation of metabolic syndrome. Indinol used to treat both hormone-dependent and hormone-independent BC showed an antimetabolic effect that was most pronounced 6 months later. Conclusion. Thus, early correction of metabolic disturbances with antimetabolites is one of the important, pathogenetically sound areas in the prevention of BC.